Hybrid Mismatch Arrangement: Does it endanger tax base? - Irawan, Ferry; Muamarah, Hanik Susilawati; Hastuti, Dina Faqih (International Journal of Psychosocial Rehabilitation, 2020)
Base erosion and profit shifting (BEPS) action plans issued by OECD and supported by G-20 have been partially adopted by Indonesia Tax Authority (ITA). So far, Indonesia has established regulation which addressed the Action Plans. There are various ways to avoid the tax. One of the common practice is hybrid mismatch arrangement. A group of companies can obtain benefits from this transaction by making use of tax regulation in different countries. The objective of this study is to elaborate how hybrid mismatch arrangement applied and why the tax authority concern about it. This study use case-study method. We analyze a state-owned enterprises case that applied hybrid mismatch arrangement. Thus, we found several decisive results. First, Company used hybrid mismatch arrangement scheme to shift profit abroad which implied to less tax payment in Indonesia. Second, the dispute is brought to the tax court and transfer pricing became the settlement of the scheme. This is happened because Indonesia faced legal basis to treat the scheme as a hybrid mismatch arrangement. These findings may give recommendation to Indonesia Tax Authority to establish the relevant rules.